Plan de mantenimiento preventivo de infraestructura en el Instituto Tecnológico de Costa Rica - Brenes-Ugalde, Daniel (Instituto Tecnológico de Costa Rica, 2007)
of a preventive maintenance plan for the I.T.C.R headquarters. The institution does not have a preventive plan properly planned and in most cases only apply corrective actions to the events, to carry out this work is the maintenance department of administration (D.A.M). For their preparation took into consideration the requests that came to the maintenance department of January 1 to June 30, 2007, because of this that we do not currently have a driver's record of the activities that were mostly actions remedial. The development of the project assesses the functioning of D.A.M, according to an analysis of procedures for the processing of work orders and purchase of materials or equipment. It also evaluates the functioning of the cave. In analyzing these cases using the law from 80-20, was to identify the main hotbeds of action that must be dealt with. It is obtained by applying the plan to 46% of cases are reducing by 82.23% of the total incidence of events. These results are compiled by the preventive program for these trouble spots.
Proyecto de Graduación (Licenciatura en Ingeniería en Costrucción). Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2007.
Keywords: Mantenimiento preventivo; Mantenimiento correctivo; Diagnóstico; Análisis; Edificios